Boosting the Self‐Trapped Exciton Emission in Alloyed Cs2(Ag/Na)InCl6 Double Perovskite via Cu+ Doping. Issue 7 (17th January 2022) - Cheng, Xingwen; Xie, Zhi; Zheng, Wei; Li, Renfu; Deng, Zhonghua; Tu, Datao; Shang, Xiaoying; Xu, Jin; Gong, Zhongliang; Li, Xingjun; Chen, Xueyuan
Abstract: Fundamental understanding of the effect of doping on the optical properties of 3D double perovskites (DPs) especially the dynamics of self‐trapped excitons (STEs) is of vital importance for their optoelectronic applications. Herein, a unique strategy via Cu + doping to achieve efficient STE emission in the alloyed lead‐free Cs2 (Ag/Na)InCl6 DPs is reported. A small amount (1.0 mol%) of Cu + doping results in boosted STE emission in the crystals, with photoluminescence (PL) quantum yield increasing from 19.0% to 62.6% and excitation band shifting from 310 to 365 nm. Temperature‐dependent PL and femtosecond transient absorption spectroscopies reveal that the remarkable PL enhancement originates from the increased radiative recombination rate and density of STEs, as a result of symmetry breakdown of the STE wavefunction at the octahedral Ag + site. These findings provide deep insights into the STE dynamics in Cu + ‐doped Cs2 (Ag/Na)InCl6, thereby laying a foundation for the future design of new lead‐free DPs with efficient STE emission. Abstract : A strategy of Cu + doping is proposed to boost the self‐trapped exciton (STE) emission in alloyed Cs2 (Ag/Na)InCl6 double perovskites, with photoluminescence (PL) quantum yield increasing from 19.0% to 62.6% and excitation band shifting from 310 to 365 nm. Mechanistic investigation reveals that the remarkable PL enhancement stems from the increased radiative recombination rate and density of STEs.